Peran TNI AL dan BAKAMLA dalam Menjaga Kedaulatan Laut di Wilayah Perbatasan Papua Selatan sebagai Implementasi Asta Cita - Muhammad Saiful Fahmi; Burhanuddin Burhanuddin; Ricardo Goncalves Klau; Andi Ervin Novara Jaya; Ilham Majid (Lembaga Yasin AlSys, 2025)
As the world’s largest archipelagic state, Indonesia possesses vast and strategically important maritime areas, including the southern Papua maritime border adjacent to Australia and Papua New Guinea, which is vulnerable to sovereignty violations such as illegal fishing, smuggling, and border incursions. This study examines the role of the Indonesian Navy (TNI AL) as the main component of national defense in Indonesian jurisdictional waters in safeguarding the territorial integrity of the Unitary State of the Republic of Indonesia (NKRI) and securing sea lines of communication and national interests from various threats, while also analyzing the role of the Indonesian Maritime Security Agency (Bakamla), particularly the Bakamla Station in Merauke, as a non-military maritime security and safety guardian operating through the Indonesia Maritime Patrol system. The research employs an empirical juridical approach by reviewing key regulations, including Law Number 34 of 2004 on the Indonesian National Armed Forces (TNI) as last amended by Law Number 3 of 2025 on the TNI, Law Number 32 of 2014 on Maritime Affairs, and Presidential Regulation Number 178 of 2014, and by analyzing the implementation of these legal frameworks in society. The findings show that TNI AL and Bakamla (Bakamla Station Merauke) constitute the front line of national maritime security in line with Indonesia’s national development vision as articulated in Asta Cita, particularly its second pillar on consolidating the national defense and security system. However, optimalizing the role of these two institutions is still constrained by limited resources, the complex geopolitical dynamics of the southern Papua border area, and regional sentiments in the Asia–Pacific. These findings underscore the importance of strengthening institutional capacity, enhancing inter-agency coordination, and updating maritime security strategies to support the realization of a robust maritime defense posture that is responsive to the evolving threat landscape in border regions.